Social Performance Vs Financial Performance of Microfinance Institutes (MFIs) In Cameroon: Case of MFIs Affiliated to Mutelles Communautaires de Croissance (MC²) (International Journal of Scientific Research and Management (IJSRM), 2022)
Microfinance is a means of the struggle against poverty in developing countries like Cameroon through financing activities that generate incomes for poor households. The issue regarding the best way to provide financial services to the poor has fuelled intensive debates between two different schools of thought: Institutionalists and Welfarists. This debate faces two requirements of microfinance: Targeting the poorest among the poor (social performance) and enhancing the profitability of the institution (financial performance). The main objective of this paper is to asses if there is mutuality between Social Performance(SP) and Financial Performance(FP) or there is trade-off between Social Performance and Financial Performance of Microfinance Institutions. To attain our objectives, the methodology used was that based on the estimation of panel data for the retained model for the period of 2016-2019. Secondary source was used to collect data from 37 MFIs affiliated to MC2 and analysed using a computerized data analysis package known as SPSS 11.0 and the following results were obtained: the findings shows that there exist a relationship between social performance and financial performance when certain variable like return to equity at 10% is considered which is in conformity with Joseph Nzongand and al.(2013) findings and when the engagement in favour of the related committed is consider as a variable, the finding shows that there is no relationship between SP and FP neither at 1% or 5% nor 10% which ties with the findings of Djamaman Brice Gaétan (2012). After our findings, some recommendation were made of which include; information concerning the number of women who are in real terms borrowers could be treated as an important aspect so as to provide a solid information background for research such as ours, then further study in such work will be more grounded.